Dietary steviol glycosides mixture supplementation modulates the gene expression of gut chemoreceptors and enhances the antioxidant capacity in weaned piglets - Yunxia Xiong; Zhentao He; Qiwen Wu; Hao Xiao; Shuting Cao; Xuefen Yang; Yajing Li; Zongyong Jiang; Cui Zhu; Li Wang (Porcine Health Management)
Abstract Background Stevia glycosides (SGs) have been widely used as an ideal sugar alternative in the food industry. However, the potential application of SGs mixture in the diets of weaned piglets remains unexplored. This study aimed to investigate the effect of dietary SGs mixture supplementation on growth performance, gene expression of gut chemoreceptors, and antioxidant capacity in weaned piglets. Methods A total of 216 weaned piglets (Duroc × Landrace × Yorkshire, 7.36 ± 0.04 kg body weight) were randomly assigned to 6 groups (6 pens/group with 6 piglets/pen), and were fed with the basal diet supplemented with 0, 100, 150, 200, 250, or 300 mg/kg SGs mixture for 42 days. The serum, liver, longissimus thoracis, and jejunal samples were collected on day 43. Results The results showed that inclusion the SGs mixture in the diet did not have a significant impact on growth performance from days 1 to 28 (P > 0.05). But increasing the concentration of SGs mixture tended to linearly decrease the average daily gain from days 1 to 42 (P = 0.052). However, 150 mg/kg SGs mixture supplementation significantly increased the mRNA expression of taste receptor family 1 member 2 (T1R2) and glucose transporters 2 (GLUT2) in the jejunum (P < 0.05), while 150 and 200 mg/kg SGs mixture supplementation significantly increased T1R3 mRNA expression (P < 0.05). Moreover, 150 mg/kg SGs mixture supplementation significantly reduced serum malondialdehyde content (P < 0.05). Increasing the concentration of SGs mixture linearly and quadratically increased serum total superoxide dismutase (T-SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activity, as well as hepatic T-SOD, GSH-Px activity, and muscle total antioxidant capacity contents (P < 0.05). Furthermore, piglets fed a diet supplemented with 100 mg/kg SGs mixture had higher serum T-SOD, CAT, and GSH-Px activities compared with the other treatments (P < 0.05). Conclusions Therefore, our results suggest that dietary 100 ~ 150 mg/kg SGs mixture supplementation modulates gene expression of sweet taste recognition receptors and glucose transporters, while also enhancing the antioxidant capacity of weaned piglets.